DECADES IN REVIEW: A BIBLIOMETRIC ANALYSIS OF GLOBAL AND CHINESE RESEARCH ON COLLEGE ENGLISH TEACHING (2003-2022) - Ming, Zhang Wei (Top Educational Review Journal (TERJ), 2023)
College English courses are foundational for nearly all college students in China. The landscape of College English teaching in China has undergone iterative reforms, leading to a persistent debate between academic English and general English. While these reforms have generally enhanced university English teaching, there has been a tendency to overemphasize model constructs in college English teaching research. In response to the evolving integration of college English cultural teaching models and modern information technology, several scholars have endeavored to create intelligent systems that extend the reach and depth of modern information technology in college English cultural education. These initiatives unlock the vast potential of modern information technology, paving the way for innovative directions in college English cultural teaching. This paper draws upon the work of Zhang and others who have identified effective methods for teaching English using mobile devices. By synthesizing these advancements, the paper contributes to the ongoing discourse surrounding the optimal blend of technology and pedagogy in college English teaching, while maintaining scientific and efficient approaches.